2021
DOI: 10.1292/jvms.21-0113
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis seroprevalence and comparison of hematology and biochemistry parameters between seropositive and seronegative captive Asian elephants of Nepal

Abstract: We conducted a tuberculosis serosurveillance program of captive elephants in Nepal and compared hematology and biochemistry parameters between seropositive and seronegative elephants. A total of 153 elephants (male=20, female=133) from four national parks were tested for TB using the ElephantTB STAT-PAK ® Assay (ChemBio Diagnostic Systems, Inc., Medford, NY, U.S.A.). The mean reported age for 138 elephants was 38.5 years (range 2-71 years).Seroprevalence for TB was 21.56% (33/153). The majority of seropositive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“… Malaysia Asian elephant Captive 23.30% Univariate analysis showed that elephants with assigned mahouts have significantly higher risk of TB OR = 3.8 The risk of seroconversion was significantly higher among elephants with assigned mahouts [OR = 4.9] 10 Magnuson et al (2017) [ 41 ] Clinical research Culture and Molecular Culture, PCR USA Asian elephant Captive 8.40% Molecular test results can be used to support current diagnostic procedures applied by veterinarians for treatment decisions to prevent the spread of tuberculosis in elephants. 11 Rosen et al (2018) [ 10 ] Cross sectional study Serology Elephant TB Stat-Pak and DPP VetTB Assay Zimbabwe African elephant Captive 17.10% Strong correlations were noted between contact with wild elephants and facilities ( p = 0.86) 12 Jeewan et al (2021) [ 35 ] Cross sectional study Serology Elephant TB Stat-Pak Nepal Asian elephant Captive 21.56% The occurrence of TB seropositive cases in other more remote national parks suggest TB may be wide spread among the captive elephant population of Nepal PCR Polymerase chain reaction, ELISA Enzyme-linked immunosorbent assay, TB Tuberculosis …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Malaysia Asian elephant Captive 23.30% Univariate analysis showed that elephants with assigned mahouts have significantly higher risk of TB OR = 3.8 The risk of seroconversion was significantly higher among elephants with assigned mahouts [OR = 4.9] 10 Magnuson et al (2017) [ 41 ] Clinical research Culture and Molecular Culture, PCR USA Asian elephant Captive 8.40% Molecular test results can be used to support current diagnostic procedures applied by veterinarians for treatment decisions to prevent the spread of tuberculosis in elephants. 11 Rosen et al (2018) [ 10 ] Cross sectional study Serology Elephant TB Stat-Pak and DPP VetTB Assay Zimbabwe African elephant Captive 17.10% Strong correlations were noted between contact with wild elephants and facilities ( p = 0.86) 12 Jeewan et al (2021) [ 35 ] Cross sectional study Serology Elephant TB Stat-Pak Nepal Asian elephant Captive 21.56% The occurrence of TB seropositive cases in other more remote national parks suggest TB may be wide spread among the captive elephant population of Nepal PCR Polymerase chain reaction, ELISA Enzyme-linked immunosorbent assay, TB Tuberculosis …”
Section: Resultsmentioning
confidence: 99%
“… 25 Greenwald et al (2009) [ 45 ] Asian and African elephant Captive Europe and the USA Elephant to Humans and other animals Rapid and accurate antibody tests to identify infected elephants will likely allow earlier and more efficient treatment, thus limiting the transmission of infection to other susceptible animals and to humans. 26 Mikota et al (2000) [ 15 ] Asian Elephant Captive and Free-ranging USA Elephant and human Further research is essential to validate other diagnostic test and treatment protocols 27 Jeewan et al(2021) [ 35 ] Asian elephant Captive Nepal Between elephant to other hosts, including humans Include blood parameters in future TB surveillance studies. MTB M. tuberculosis , ELISA enzyme-linked immunosorbent assay, TB tuberculosis …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This poses a serious risk of zooanthroponosis and disease to both captive and wild elephant populations, as well as a risk to humans given the possibility of bidirectional transmission (15,22). A recent study in four national parks in Nepal showed a high seroprevalence (21.56%) of TB in captive elephants, with most cases detected in Chitwan National Park (23). In addition, some evidence of zooanthroponosis has been reported from previous studies in Nepal that also isolated M. tuberculosis from diseased elephants using multilocus variable number of tandem repeats (MLVA) (15,24), large sequence polymorphism (24) or whole genome data (25).…”
Section: Introductionmentioning
confidence: 99%